The spread of COVID-19 in six western metropolitan regions: a false myth on the excess of mortality in Lombardy and the defense of the city of Milan - Signorelli, Carlo; Odone, Anna; Gianfredi, Vincenza; Bossi, Eleonora; Bucci, Daria; Oradini-Alacreu, Aurea; Frascella, Beatrice; Capraro, Michele; Chiappa, Federica; Blandi, Lorenzo; Ciceri, Fabio (Acta Biomedica Atenei Parmensis, 2020)
We analyzed the spread of the COVID-19 epidemic in 6 metropolitan regions with similar demographic characteristics, daytime commuting population and business activities: the New York metropolitan area, the Île-de-France region, the Greater London county, Bruxelles-Capital, the Community of Madrid and the Lombardy region. The highest mortality rates 30-days after the onset of the epidemic were recorded in New York (81.2 x 100,000) and Madrid (77.1 x 100,000). Lombardy mortality rate is below average (41.4 per 100,000), and it is the only situation in which the capital of the region (Milan) has not been heavily impacted by the epidemic wave. Our study analyzed the role played by containment measures and the positive contribution offered by the hospital care system. (www.actabiomedica.it)